c-myb supports erythropoiesis through the transactivation of KLF1 and LMO2 expression - Bianchi, Elisa; Zini, Roberta; Salati, Simona; Tenedini, Elena; Norfo, Ruggiero; Tagliafico, Enrico; Manfredini, Rossella; Ferrari, Sergio (Blood, 2010)
The c-myb transcription factor is highly expressed in immature hematopoietic cells and down-regulated during differentiation. To define its role during the hematopoietic lineage commitment, we silenced c-myb in human CD34(+) hematopoietic stem/progenitor cells. Noteworthy, c-myb silencing increased the commitment capacity toward the macrophage and megakaryocyte lineages, whereas erythroid differentiation was impaired, as demonstrated by clonogenic assay, morphologic and immunophenotypic data. Gene expression profiling and computational analysis of promoter regions of genes modulated in c-myb-silenced CD34(+) cells identified the transcription factors Kruppel-Like Factor 1 (KLF1) and LIM Domain Only 2 (LMO2) as putative targets, which can account for c-myb knockdown effects. Indeed, chromatin immunoprecipitation and luciferase reporter assay demonstrated that c-myb binds to KLF1 and LMO2 promoters and transactivates their expression. Consistently, the retroviral vector-mediated overexpression of either KLF1 or LMO2 partially rescued the defect in erythropoiesis caused by c-myb silencing, whereas only KLF1 was also able to repress the megakaryocyte differentiation enhanced in Myb-silenced CD34(+) cells. Our data collectively demonstrate that c-myb plays a pivotal role in human primary hematopoietic stem/progenitor cells lineage commitment, by enhancing erythropoiesis at the expense of megakaryocyte diffentiation. Indeed, we identified KLF1 and LMO2 transactivation as the molecular mechanism underlying Myb-driven erythroid versus megakaryocyte cell fate decision.